2016
DOI: 10.3389/fmicb.2016.00787
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus Strains of Pandemic Serotypes Identified from Clinical and Environmental Samples from Jiangsu, China

Abstract: Vibrio parahaemolyticus has emerged as a major foodborne pathogen in China, Japan, Thailand, and other Asian countries. In this study, 72 strains of V. parahaemolyticus were isolated from clinical and environmental samples between 2006 and 2014 in Jiangsu, China. The serotypes and six virulence genes including thermostable direct hemolysin (TDR) and TDR-related hemolysin (TRH) genes were assessed among the isolates. Twenty five serotypes were identified and O3:K6 was one of the dominant serotypes. The genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…The results of our study revealed that there is no consensus among the results of three methods employed for the detection of pandemic isolates. Similar observations of variance in results among the methods used for detection of pandemic strains were made by Li et al (2016) where the prevalence of GS-PCR, PGS PCR, Orf8, and HUα positive isolates were reported to be 81.9, 38.9, 16.9, and 18.9%, respectively. Another study conducted in the eastern coastal region of India reported PGS-PCR and GS-PCR positive isolates to be, respectively, 6.5% and 2.4% of pathogenic isolates (Parthasarathy et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…The results of our study revealed that there is no consensus among the results of three methods employed for the detection of pandemic isolates. Similar observations of variance in results among the methods used for detection of pandemic strains were made by Li et al (2016) where the prevalence of GS-PCR, PGS PCR, Orf8, and HUα positive isolates were reported to be 81.9, 38.9, 16.9, and 18.9%, respectively. Another study conducted in the eastern coastal region of India reported PGS-PCR and GS-PCR positive isolates to be, respectively, 6.5% and 2.4% of pathogenic isolates (Parthasarathy et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…Another striking observation is the appearance of tdh − trh + isolates carrying the toxRS/ new + pandemic marker. Pandemic strains of V. parahaemolyticus are mostly associated with the tdh gene with few reports of GS-positive trh-containing isolates from clinical cases [23,37,38]. Data pertaining to the pandemic status of environmental trh-positive V. parahaemolyticus is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…PCR assays to amplify the pandemic markers were performed using specific primers previously reported to detect toxRS/new [ 11 ] and orf8 sequence [ 18 ]. The PCR cycling parameters for these assays were as follows: for the toxRS/new gene, initial denaturation at 94°C for 3 min, followed by 25 cycles of 30s at 94°C, 30s at 45°C, and 1 min at 72°C, with a final extension of 5 min at 72°C, and for the orf8 gene, denaturation at 96°C for 5 min, followed by 25 cycles of 1 min at 94°C, 1 min at 53°C, and 1 min at 72°C, with a final extension of 7 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%